Halmstads Tivoli - Ericson, Johanna (2007)
During the late 19: th century the park Tivoli in Halmstad, today called Norre Katts park, was known as one of the most beautiful amusementparks of southern Sweden. This is a description that hardly anyone would use to portray the park today. The aim of this study is therefore to investigate what the park once looked like and how it has changed until today's neglected state. The history of the place and by who and for whom the park with; 4 ½ acers with meandering paths, caves, an avenue, leaf halls and bowers, was created.